Bulky Counterions: Enhancing the Two‐Photon Excited Fluorescence of Gold Nanoclusters. Issue 2 (20th December 2017) - Bertorelle, Franck; Moulin, Christophe; Soleilhac, Antonin; Comby‐Zerbino, Clothilde; Dugourd, Philippe; Russier‐Antoine, Isabelle; Brevet, Pierre‐François; Antoine, Rodolphe
Abstract: Increasing fluorescence quantum yields of ligand‐protected gold nanoclusters has attracted wide research interest. The strategy consisting in using bulky counterions has been found to dramatically enhance the fluorescence. In this Communication, we push forward this concept to the nonlinear optical regime. We show that by an appropriate choice of bulky counterions and of solvent, a 30‐fold increase in two‐photon excited fluorescence (TPEF) signal at ≈600 nm for gold nanoclusters can be obtained. This would correspond to a TPEF cross‐section in the range of 0.1 to 1 GM. Abstract : Chain my heart : By an appropriate choice of bulky counterions and of solvent, a 30‐fold increase in two‐photon excited fluorescence signal at ≈600 nm for gold nanoclusters can be obtained.